Preparation of rice straw-waste tire dust composite board - Muhammad Syafiq Azmi
In this final year project, agricultural lignocelluloses fiber (rice straw) and waste tire dust composite board were prepared using the method use in the wood-based panel industry. The manufacturing parameters were density (0.66g/cm3, 0.64 g/cm3, 0.60 g/cm3) and rice straw content(10/90, 20/80 and 30/70) weight of rice straw/waste tire dust of 10,20 and 30wt%.